ELT in the Margins: A Competency-Based Inquiry into Blended English Instruction in Maluku's Outer Regions: - Franklin Untailawan; Asweres A. F Termas (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
This study investigates the effectiveness and challenges of integrating blended learning and competency-based approaches in English language teaching (ELT) in remote areas of Maluku. Limited access to educational resources, including instructional materials and teacher training, remains a major constraint affecting learning quality. A competency-based approach emphasises measurable English skills and learning outcomes, while blended learning combines face-to-face instruction with digital technologies to enhance flexibility and access. Using a qualitative case study design, data were collected through classroom observations, interviews with teachers and students, and analysis of curriculum documents in several remote schools. The findings indicate that competency-based blended learning has the potential to reduce geographical barriers and promote more active student engagement. However, its implementation is hindered by inadequate technological infrastructure, limited teacher digital competence, and challenges in aligning the curriculum with local contexts and national standards. This study highlights the need for sustained policy support, continuous teacher professional development, and stakeholder collaboration to improve the quality of ELT in marginalised regions.